1998
DOI: 10.1021/jp9824050
|View full text |Cite
|
Sign up to set email alerts
|

The Complexation of Tetracycline and Anhydrotetracycline with Mg2+ and Ca2+:  A Spectroscopic Study

Abstract: Steady-state absorption and emission, circular dichroism (CD), and time-of-flight secondary-ion-mass-spectroscopic (TOF−SIMS) measurements were performed to study the complexation of tetracycline (TC) and anhydrotetracycline (AHTC) with Mg2+ and Ca2+ ions, respectively, in aqueous solutions at pH 8.02. The results obtained suggest that Ca2+ forms a 1:2 ligand:metal complex with TC via chelation through O10−O11 and O12−O1 and induces thereby the extended conformation A of TC, which is stabilized through hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(124 citation statements)
references
References 37 publications
(134 reference statements)
3
109
0
3
Order By: Relevance
“…In study a conducted by Wessels et al the results obtained suggest that Ca 2+ forms a 1:2 ligand: metal complex with TC. 9 In current study, by both the methods we found that oxytetracycline chelates calcium and these findings are comparable with earlier studies. The base line calcium concentration was found to be 10 mg/dl.…”
Section: Discussionsupporting
confidence: 93%
“…In study a conducted by Wessels et al the results obtained suggest that Ca 2+ forms a 1:2 ligand: metal complex with TC. 9 In current study, by both the methods we found that oxytetracycline chelates calcium and these findings are comparable with earlier studies. The base line calcium concentration was found to be 10 mg/dl.…”
Section: Discussionsupporting
confidence: 93%
“…The difference between the d-spacings of TC-intercalated and TC-dehydrated birnessite is about 4.3 Å . Generally accepted conformations for TC were extended and twisted forms, with the former primarily existing in basic solution when the dimethylamino group lies below the plane spanned by the ring system (Wessels et al 1998), while the latter was present in acidic-to-neutral solutions when the dimethylamino group lies above the ring system (Wessels et al 1998;Duarte et al 1999;Othersen et al 2003). In the twisted form, TC was 12.9 Å long, 7.5 Å wide, and 6.2 Å high, occupying an area of 97 Å 2 when the ring was parallel to the surface (Gambinossi et al 2004).…”
Section: Xrd Analysesmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Nesse contexto, estudos teóricos têm sido realizados por alguns de nós, relacionados à interação do derivado 5a,6-anidrotetraciclina (AHTC) com cátions metálicos. [42][43][44][45][46] Esses trabalhos têm auxiliado os experimentalistas nas propostas para os possíveis sítios de coordenação, como evidenciado nos trabalhos de Wessels et al 47 e Vogler et al, 40 envolvendo complexos de AHTC com Mg(II) e Pt(II), respectivamente.…”
Section: Figura 1 Estruturas Das Principais Tetraciclinas Usadas Na unclassified